The Highland and the Coast - An Analysis of the Current Conflict in Cabo Delgado. A conversation between Yussuf Adam and Carmeliza Rosário - Yussuf Adam; Carmeliza Rosario (Kronos)
Yussuf Adam's doctoral thesis ends with a short story collected in 1981 in the village of Mualela, on the Mueda plateau. In it, the president of the village speaks of the marriage of Mary, God's daughter, as a metaphor for the post-independence dynamics, where the solidarity of the liberation struggle gave way to feelings of injustice in the redistribution of power and benefits. Using Galtung's matrix from his Structural Theory of Revolutions, Adam argues that the dynamics that resulted in the fragilities and tensions in the post-independence came from complex multiple and interconnected causes. Specifically, there is a link between destabilisation, foreign aid and the state's development policies. Carmeliza Rosário and Adam reflect on how the same connection is visible in the processes that fostered the present conflict in Cabo Delgado. Similarly, there are limitations in the ability to produce evidence for analysis of the conflict, and the object of intellectual exercises of this nature remains the same - peace. At stake are Mozambique's aspirations as a nation and its ability to negotiate consensus between its different parties. These consistently give rise to protracted conflicts. The sharpening of differences and the worsening of the conflict has to do with explanations for conflicts based on the sentiments of betrayal, autocracy, of the external hand, exclusion, and a 'winner takes all' worldview.